Feasibility of e-module based on TPACK and microlearning in the biology curriculum review course - Dini Safitri; Ade Suryanda; Fitria Pusparini; Daniar Setyo Rini; Rizhal Hendi Ristanto; Rosi Fitri Ramadani (Universitas Muhammadiyah Malang, 2025)
The main problem is the lack of dedicated digital e-modules in the high school biology curriculum analysis course, causing students to rely solely on government documents and online sources. This research aims to develop a TPACK-based e-module enriched with microlearning strategies and test its feasibility through expert validation and user readability testing. The research uses a research and development method with the ADDIE model, which includes the stages of needs analysis, design, development, limited implementation, and evaluation. The research subjects involved three experts (content, media, and language) and student at Universitas Negeri Jakarta, classes of 2022 and 2023, who had completed the Biology Curriculum Review course. Data was collected with experts’ and users’ feasibility questionnaires, then analyzed using feasibility criteria. The result show that according to the experts review, the percentage is about 95.50% (very feasible) and according to the respondent is about 88,29% (very feasible). The e-module was highly feasible but requires improvements in design consistency, language clarity, and integration of TPACK and microlearning for greater effectiveness.